Assessing the Use of River Sand and Sawdust Ash in the Stabilization of Weak Subgrade Soils - Justine Shilla Nambooze (Uganda Christian University, 2024)
Expansive soils usually have a high compressibility they also have a tendency to shrink upon drying and swelling when wet, and high-water absorption. These expansive soils make it impossible to build civil engineering projects without adequate stability due to a number of issues they cause. In places where these soils exist, before construction of any structure, various techniques are frequently used to enhance their engineering qualities. Traditionally, common additives for stabilizing soil have included cement and lime. But in Uganda, where there is a lot of waste from the agricultural sector, and the increasing prices of these additives, there is need to use the locally available materials to stabilize these weak soils. Thus, the purpose of this study was to determine whether river sand and sawdust ash (SDA) were suitable for stabilizing expansive soils. Through carrying out experiments, the percentages of river sand and saw dust ash were varied in the following ranges; 0% river sand and 0% saw dust ash and 100% soil, 0% river sand and 12% saw dust ash, 15% river sand and 9% saw dust ash, 30% river sand and 6% saw dust ash, 45% river sand and 3% saw dust ash, 60% river sand and 0% saw dust ash with varying percentages of soil which were varied by mass. The tests were carried out which include classification tests, durability tests and strength tests. The results showed that the neat soil was a highly plastic clay soil which was poor to be used for road construction and therefore required stabilization. On addition of river sand and saw dust ash in the above proportions showed a notable decrease in the plasticity index from 30.4% for the neat soil to 5.2% at 45% river sand and 3% saw dust ash. However, at 60% river sand and 0% saw dust ash the soil matrix was non-plastic. The maximum dry density was also seen to increase until it reached its highest of 1.898 g/cm3 and a reduction in optimum moisture content to 8.1%. The results reveal the potential for the use of the combination of river sand and saw dust ash to stabilize the weak subgrade soils. The research also adds to the existing body of knowledge in that it addresses the problem of poor soils and also environmental waste concerns brought about by the agricultural sector.